PERJALANAN UMAT MANUSIA SETELAH HARI KEBANGKITAN - ., Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2022)
Human life, from the womb to death, humans will experience a similar process, which is change. At the beginning of life the change is towards growth and development, while in the end the change is towards a setback that is closed by death. Allah gave us life solely for us to carry out our obligations as khalifah on earth by carrying out his orders. Because at the end of time there will be a count of good and bad deeds for us with two different places namely Heaven and Hell. What is the natural picture of human life before the Day of Judgment? What are the natural pictures of human life after the Day of Judgment? The benefit that can be obtained through this paper is that it can increase students' knowledge and insight on the subject of Fiqh, especially regarding the description of life before and after the Day of Judgment. The last day or commonly called the hereafter is the day of the destruction of all the universe and all life in it. The last day can also be understood as the end of life in this mortal world and entering the beginning of a new eternal life in the afterlife. Thus, believing in the hereafter means to justify with all your heart that after life in this world there will be another life that is real and eternal. In that eternal life man will get the certainty of his life, whether his life will be successful and happy or vice versa his life will be wretched and miserable. Among the important events that occurred on the hereafter were the resurrection of humans from the grave, the gathering of people in Padang Mahsyar, the calculation and weighing, and the retribution of human charity, and the path that humans traveled (shirath) to go to heaven or hell. Belief in the last day is the fifth pillar of the sixth pillar of the faith. However, in the Koran and the hadith of the Prophet Muhammad. faith in the hereafter is always called hand in hand with faith in God.